Perlindungan Hukum dalam Mengantisipasi dan Menangani Kerugian Nasabah Akibat Scam Melalui Link Phising pada Mobile Banking - Indah Tri Sari Harahap; Alya Arianti Nasution; Keisya Putri Balqis; Wahyudin; Nikmah Dalimunthe (Universitas Muhammadiyah Surabaya, 2025)
With the presence of digital transformation in the financial sector, it makes significant convenience for the community, but adds to cybercrime. One of the threats that often occurs is digital fraud that uses user negligence through fake links that resemble official banking services. This research is intended to examine how legal protection to protect customers and how mechanisms to prevent and handle losses are carried out. The research method used is descriptive qualitative using a literature approach through the study of scientific journals, books, and existing laws. The results of the research show that regulations have regulated the obligations of banks when maintaining system security as well as providing a complaint mechanism for customers. That way, there are still obstacles to the application of legal protection, especially regarding low digital literacy and difficulty of proof. The research conclusion prioritizes the need to strengthen regulations, increase public education, and maximize banking responsibilities. Collaboration between regulators, banking institutions, and the community as the main foundation in shaping security, justice, and continuity in the digital banking system.